Finding Optimized Frequent Pattern using Genetic Algorithm - Pandagre, Karuna Nidhi; Veenadhari, S (International Journal of Computer Sciences and Engineering, 2019)
Data mining plays an important role for framing association rules between the huge sets of gathered data. Association between sets of items or entities in transaction, relational database and other data warehouse as well as their frequent patterns can be discovered by using association rules. However, the limitations in using association rules are that it takes too much time to figure out all the frequent itemsets. It is therefore, weblog mining techniques with Genetic Algorithms (GA) are used to find information patterns from the web data with much lesser time in comparison to association rules. By the using GA the outcome of association rule mining and behaviour analysis is improved.GA are powerful and extensively related to stochastic search and optimization technique created on the model of universal selection and evaluation. The aim of this paper is to observe all the frequent itemsets, patterns and produce the association rules from the huge datasets by use of proposed evolutionary algorithm.